India-Russia economic relations: issues and prospects - Gidadhubli, R.G. (1999)
Wide year-to-year fluctuations characterise India's trade with Russia. While that country is all set to make significant sales to India of machinery and equipment and military hardware, India has to reckon with adhocism in the manner of utilisation of the rupee hoard at Russia's disposal and bleak prospects of significantly boosting exports even of `comparative advantage' commodities. Exports to Russia may plunge once rupee trade is completely phased out. - Reproduced
Keywords: Economic relations; India - Foreign economic relations - Russia; International economic relations